Penta Herbs Forte: The Effect of PHF Extract on Superoxide Dismutase Activity in Hypoxic Sprague Dawley Rat’s Heart - Jessie Farica Gunardi; Noer Saelan Tadjudin; Frans Ferdinal; David Limanan; Eny Yulianti (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Hypoxia is a condition in which tissues receive insufficient oxygen, leading to increased production of reactive oxygen species (ROS) and triggering oxidative stress that can cause heart damage. Penta Herbs Forte (PHF), a combination of Blumea balsamifera, Curcuma xanthorrhiza, Zingiber officinale var. rubrum, Phyllanthus niruri, and Andrographis paniculata, contains bioactive compounds with antioxidant properties that may help strengthen the body’s defense against oxidative injury. This study aimed to evaluate the effect of PHF extract on the activity of the antioxidant enzyme Superoxide Dismutase (SOD) in the hearts of hypoxia-induced Sprague Dawley rats. The research included in vitro assessments (total phenolic content, BSLT toxicity, and FRAP assays) and in vivo experiments involving eight groups of rats receiving PHF extract with different hypoxia exposure durations (0, 1, 7, and 14 days). Heart tissues were processed into homogenates, and SOD activity was measure by spectrophotometry, followed by statistical analysis using the Mann-Whitney and Kruskal-Wallis tests. Although PHF groups showed higher SOD activity, significant differences between control and treated groups were observed only at 1-day hypoxia. These findings suggest that PHF may help protect the heart from hypoxia-related oxidative stress by enhancing antioxidant enzyme activity.